Hotel lobbies and lounges : the architecture of professional hospitality - Avermaete, Tom.; Massey, Anne, 1956- (New York : Routledge, 2013)
"Hotels occupy a particular place in popular imagination. As a place of exclusive sociability and bohemian misery, a site of crime and murder and as a hiding place for illicit liaison, the hotel has embodied the dynamism of the metropolis since the eighteenth century. Hotel Lounges and Lobbies: The Architecture of Professional Hospitality explores the architectural significance of hotels throughout history and how their material construction has reflected and facilitated the social and cultural practices for which they are renowned. Including case studies addressing contemporary developments in hotel planning and design, and illustrated throughout, this volume is an innovative and insightful contribution to architectural and interior design literature"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Hotel lobbies; Hotels -- Designs and plans; Architecture and society; Electronic books